Resveratrol: A molecule whose time has come? And gone? - Soleas, George J.; Diamandis, Eleftherios P.; Goldberg, David M. (Clinical biochemistry, 1997)
Objectives: Resveratrol (3,5,4′-trihydroxystilbene) is the parent compound of a family of molecules, including glucosides and polymers, existing in cis and trans configurations in a narrow range of spermatophytes of which vines, peanuts and pines are the prime representatives. Its synthesis from p-coumaroyl CoA and malonyl CoA is induced by stress, injury, infection or UV-irradiation, and it is classified as a phytoalexin anti-fungicide conferring disease resistance in the plant kingdom. Results: In vitro, ex vivo and animal experiments have shown that it possesses many biological attributes that favour protection against atherosclerosis, including antioxidant activity, modulation of hepatic apolipoprotein and lipid synthesis, inhibition of platelet aggregation as well as the production of pro-atherogenic eicosanoids by human platelets and neutrophils. Red wine represents its main source in the human diet, and it has been proposed as a major constituent of the polyphenol fraction to which the health benefits of red wine consumption have been attributed. Conclusions: The past several years have witnessed intense research devoted to its measurement in wine and the factors likely to promote its enrichment in this beverage. Up to the present, conclusive evidence for its absorption by human subjectsin biologically significant amounts is lacking, and it is questionable (but not yetexcluded) that its powerful and beneficial in vitro activities are reproduced as a consequence of sustained moderate red wine consumption.